Computer Assisted School Administration (CASA) : Factors Crucial For The Success Of Its Implementation At Fully Residential Schools In Kedah Darul Aman - Muhammad Zaini, Mohd. Zain (1997)
The purpose of this study is to investigate the developmental stage of Computer Assisted School Administration (CASA), factors crucial to the success of its implementation, and its strengths and weaknesses at fully residential schools (SBPs) in the state of Kedah Darul Aman. The methodology used included case study, survey and literature review. Three cases (SBPl, SBP2 and SBP3) were studied and compared. Much of the background of this study is obtained from the literature review. A total of 21 subjects, school administrators ranging from principals to senior subject teachers, were involved in the survey. Descriptive analysis was used to process the data. It was found that SBPl, SBP2 and SBP3 are in the expansion, integration and initiation stages respectively. All three cases revealed that only staff attitude is perceived to be a crucial success factor of CASA implementation. The strengths of CASA were identified as adequate computer facilities, fair distribution of administrators’ demography, fully utilised computer networking (LAN), computer literate administrators and access to the INTERNET. Its weaknesses, however, are in contrast to its strengths except for no integration among the areas of computer application and an uninitiated managerial behaviour. The result of the findings can aid other schools (SBPs, in particular) considering to indulge their administrative system with CASA.